The Burden of Head Injuries in Iran from 1990 to 2019: Findings from The Global Burden of Disease Study 2019 - Maleki, Tahereh; Baigi, Vali; Safari, Negin; Sharif-Alhoseini, Mahdi (Archives of Academic Emergency Medicine, 2024)
Introduction: Head injuries (HI) pose a significant public health concern globally, impacting morbidity, mortality, and economic burden. This study aimed to evaluate the epidemiology and trends associated with head injuries in Iran from 1990 to 2019. Methods: Our study, based on data from the Global Burden of Diseases (GBD) Study 2019, undertook a comprehensive comparison of the burden of HI in Iran with the Middle East and North Africa (MENA) and global benchmarks. We assessed the incidence, prevalence, and years lived with disability (YLD) through various metrics, including absolute numbers, age-standardized rates (ASR), percentage changes, and estimated annual percentage changes (EAPC) from 1990 to 2019. Results: The incidence of HI in Iran decreased significantly from 1990 to 2019, with a notable reduction compared to MENA and global trends (EAPC: -1.44, 0.71, and -0.11, respectively). Prevalence showed a declining trend (EAPC: -1.00), with a slight increase in YLDs (EAPC: 0.12). Notable peaks in HI incidence coincided with natural disasters, notably the 1990 Manjil-Rudbar earthquake and the 2003 Bam earthquake. Conclusion: Our study reveals a decline in the overall burden of HI in Iran over the study period. To sustain this positive trend and minimize the impact of HI on public health and socioeconomic well-being, policy efforts should be directed toward ongoing prevention, early detection, and preparedness for natural disasters.